Forensic evidence: a rethinking about its use and evidential weight in Islamic Jurisprudence - Haneef, Sayed Sikandar Shah (2010)
Forensic evidence has emerge as one of the important tools to connect an accused to the crime for which he is charged and to identify him in case he is of mysterious identity. Its role is also crucial in affirming material facts relevant to issues contested before a court in civil suit. It has become indispensable in the process of implementing justice in the Western legal systems. In the Islamic jurisdictions, on the other hand, although its use and admissibility has been attempted – its evidential weight continues to invoke juristic discourses and legal theorization. It is often classified as a kind of qarinah whose admissibility as a mode of proof has invoked the same polemics that surrounds qarinah itself. This essay, however, argues: first, forensic evidence ipso facto represents an expert opinion from forensic scientists. It is as such derives its legitimacy from the Islamic sources as a separate method of proof. Second, it as a means of proof is another sure way of establishing the truth (al-bayyinah) – distinct from qarinah. It, in terms of standard and evidential weight, amounts to oral testimony perceived and revealed through scientific eyes as it unlike qarinah not only gives rise to suspicion and conjecture but affirmatively proves and disproves facts and relevant facts. Lastly, in terms of function it not only tracks and traces the physical evidence against the accused in a criminal trial, it also discloses other issues of psycho anthropological relevance to all types of cases. Accordingly, a thoughtful reflection about the reality of forensic evidence, as argued above would broaden our horizon of thinking about the ways that legal justice could obtain today.